CD8+ T Cells: GITR Matters. (30th April 2012) - Ronchetti, Simona; Nocentini, Giuseppe; Petrillo, Maria Grazia; Riccardi, Carlo
Abstract : As many members of the tumor necrosis factor receptor superfamily, glucocorticoid-induced TNFR-related gene (GITR) plays multiple roles mostly in the cells of immune system. CD8 + T cells are key players in the immunity against viruses and tumors, and GITR has been demonstrated to be an essential molecule for these cells to mount an immune response. The aim of this paper is to focus on GITR function in CD8 + cells, paying particular attention to numerous and recent studies that suggest its crucial role in mouse disease models.